Digital India-Communication Policy, Issues and Challenges - Bharthur, Sanjay (Lumina, 2020)
Erstwhile faith and belief in media and its potential for development spurred the growth of broadcasting to its present level in India. The arrival of printing press in the early phase of European colonialization subsequently lead to print journalism that is now more than 240 years old. Its sustained growth and coexistence with the new media in digital India is contrary to developments in many other nations where erstwhile print journalism is giving way to convergent media. Reforms in the telecom sector and corresponding institutional arrangements have led to the formulation of an ambitious digital India programme. This programme focusses more on enhancing the access and equity to the rural population. The nebulous distinction between legacy media and social media has raised several issues including governance, production and consumption of content and delivery of welfare services including financial inclusion. These challenges are sought to be addressed through the digital infrastructure. Solving contemporary problems within the fragile and vulnerable social structure are daunting including the challenges posed by user generated content. The frequency of internet shutdowns across the country including conflict zones has increased. A key economic and commercial variable in Digital India is the media and entertainment (M&E) industry that has taken full advantage of infrastructure b evolving newer revenue models in the over the top (OTT) platforms and smart devices. India’s communication policy in a digital context will be examined as a national case study by drawing parallels where possible with one or two other BRICS nations.